The Representation of Women as the Other in 21st Century English Songs - Safira, Rahma; Sudjatnika, Tenny; Nurrachman, Dian (Jurnal Ragam Pengabdian, 2026)
This study examines the representation of women as "the Other" in 21st-century English popular music through the lyrical narratives of Lily Allen, Pink, Paris Paloma, Halsey, and Taylor Swift. Employing a qualitative descriptive method rooted in textual and feminist literary analysis, the research utilizes Simone de Beauvoir's existentialist feminism and a mimetic approach to deconstruct how female subjectivity, immanence, and patriarchal constraints are textually constructed. The analysis focuses on selected tracks, including Stupid Girls, Hard Out Here, The Man, Labor, and Nightmare. The findings reveal that the concept of "the Other" remains deeply entrenched in contemporary popular culture, operating through three distinct forms: confinement to domestic immanence, performative hyper-femininity, and structural double standards in the professional sphere. These songs expose how modern women are still systematically reduced to supportive roles, objectified based on physical appearance, and denied equal authority despite formal emancipation. However, this study also highlights that these musical narratives do not merely reproduce traditional gender hierarchies. By employing irony, visceral resistance, and non-compliant identities, the lyrics function as critical cultural spaces for female agency, articulating resistance against patriarchal structures and reclaiming autonomous subjectivity.